(De-)Professionalisierung durch Schulpraxis Rekonstruktionen zum Studierendenhabitus und zu studentischen Entwicklungsaufgaben - Kahlau, Joana (Dokumentarische Schulforschung, 2023)
When looking at the process of extending the practical phases within teachers' training, the question of its impact on students' professionalisation becomes increasingly important. The given study distances itself from normative positions promoting an unquestioned positive effect of these practical experiences. Instead, the focus will be on the question if or to what extent practical experiences lead to a process of professionalization for future teachers. In order to tackle this question, narrative interviews have been conducted with students in teachers training who have signed in for a so-called "Studien-Praxis-Projekt", wherein these students cooperate with teachers working on a specific problem regarding school and lesson planning development. The interviews, which have been analysed using the documentary method, provide new insights into two different areas, the student's habitus - as a transitional phase between the pupil's and the teacher's habitus - and specific developmental tasks of students in teachers training. Furthermore, the results illustrate a correlation between a specific student habitus on the one hand and the way students deal with developmental tasks on the other hand. Not only can we draw conclusions about the different types of professionalisation from these data, but also it is possible to deduce the potential of professionalization for these different types. In conclusion, one can define subject-based competence as the centre of, reflection as the means and a so-called 'in between' as the place of students' professionalisation.